The Effect of Corporate Governance, Financial Performance, and Financial Slack on Green Banking - Kusumawardani, Flavia; Achmad, Chaerul; Nur Hadiyati, Siti (DINASTI RESEARCH, 2025)
Bank Indonesia regulations have required the banking industry to implement green banking practices to advance sustainability aspects that beneficial for the environment. Examining the relationship between green banking and corporate governance, financial performance, and financial slack is the focus of this study. Quantitative methods are employed in this study. With the use of a purposive sampling approach, 80 samples were collected from 21 different banks that were listed on the Indonesia Stock Exchange for the year 2019–2023. Statistical Package for the Social Sciences (SPSS) version 29 was utilized to evaluate the data via multiple linear regression approaches. The findings indicated that simultaneously corporate governance, as represented by the board of directors, board of commissioners, and independent commissioners, significantly influenced green banking. Partially, corporate governance, as represented by the board of commissioners, significantly influences green banking disclosure; nevertheless, the board of directors, independent commissioners, financial performance, and financial slack do not impact green banking disclosure.